Monitoring transient cell-to-cell interactions in a multi-layered and multi-functional allergy-on-a-chip system. Issue 11 (9th May 2019) - Rothbauer, Mario; Charwat, Verena; Bachmann, Barbara; Sticker, Drago; Novak, Richard; Wanzenböck, Heinz; Mathies, Richard A.; Ertl, Peter
Abstract : Multi-functional LOC for transient allergy monitoring. Abstract : We have developed a highly integrated lab-on-a-chip containing embedded electrical microsensors, μdegassers and pneumatically-actuated micropumps to monitor allergic hypersensitivity. Rapid antigen-mediated histamine release ( e.g. s to min) and resulting muscle contraction (<30 min) is detected by connecting an immune compartment containing sensitized basophile cells to a vascular co-culture model.